Green high-magnification foaming microsphere and preparation method thereof
Green high-ratio radiate was prepared by suspending polymerization technology using components such as polyvinyl alcohol, methyl methacrylate, butyl acrylate and 1,3,5-triacryloylhexahydro-1,3,5-triazine, etc. The foaming microspheres solve the problem of using hazardous chemicals in the prior art and achieve efficient and economical high-rate foaming effect.
Patent Information
- Application Number
- CN202411402975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing thermal expansion physical foamed microsphere technology, in order to improve the isolation and mechanical properties of the microsphere shell, dangerous chemicals methacrylonitrile or vinylidene chloride are often used, which leads to complex production and high cost, and is difficult to achieve in China. Mass production, how to use cheap monomers to prepare foamed microspheres that are resistant to high temperature and high magnification has become a challenge.
Polyvinyl alcohol, methyl methacrylate, butyl acrylate, 1,3,5-triacryloylhexahydro-1,3,5-triazine and modification initiator are used to pass suspension polymerization and cross-linking. The reaction is to form a polymer shell wrapped foaming agent, prepare green high-ratio foamed microspheres, avoiding the use of methacrylonitrile and vinylidene chloride.
A safe and environmentally friendly production process is achieved, cost is reduced, and the mechanical properties, thermal stability and gas barrier properties of the polymer are improved by forming a dense crosslinking network, significantly improving the stability and expansion ratio of foamed microspheres.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foamed microspheres, and particularly relates to green high-magnification foamed microspheres and a preparation method thereof. Background Art
[0002] Foamed microspheres, also known as expanded microspheres, are a core-shell structure material with a shell material of thermoplastic polymer (such as polymethacrylonitrile, etc.) and a core material of low-boiling point organic solvent (such as butane, pentane, etc.). The normal particle size is between 1-100μm. When heated (80-200℃), the shell softens and the low-boiling point organic solvent vaporizes from liquid to expand the shell. At the same time, the core-shell structure is not destroyed, thereby achieving a foaming effect. Foamed microspheres can help industrial products achieve lightweight, heat-insulating, and sealing properties. They are widely used in many subdivided fields and have a profound impact on people's lives.
[0003] At present, in the existing thermal expansion physical foaming microsphere technology at home and abroad, in order to improve the isolation and mechanical properties of the microsphere shell, most of them use methacrylonitrile or vinyl chloride as the main monomer, but methacrylonitrile and vinyl chloride are both hazardous chemicals, and the production process of methacrylonitrile is complicated and expensive. Only a few countries such as Japan and Germany have achieved mass production. Chinese companies still rely on imports, which increases the cost of foaming microspheres. Therefore, how to use cheap monomers instead of methacrylonitrile to prepare high-temperature resistant and high-ratio foaming microspheres is a technical problem that needs to be solved at present, and the foaming microspheres obtained will have good economic value. Summary of the invention
[0004] The purpose of the present invention is to provide a green high-magnification foamed microsphere and a preparation method thereof to solve the problems in the background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing green high-magnification foamed microspheres comprises the following steps:
[0007] (1) adding polyvinyl alcohol and sodium chloride to deionized water to dissolve, and then stirring at 1000 r / min for 5 minutes to obtain an aqueous phase; adding methyl methacrylate, butyl acrylate, a crosslinking agent and a modified initiator to a foaming agent and mixing them uniformly to obtain an oil phase;
[0008] (2) slowly adding the oil phase to the water phase at a temperature of 8-10° C. and stirring at a speed of 2000-3000 r / min for 5 min to obtain an oil-in-water suspension dispersion;
[0009] (3) Pour the suspended dispersion into a reaction kettle, introduce nitrogen and then evacuate for 3 cycles, then introduce nitrogen to increase the pressure in the kettle to 0.5-0.8 MPa, react at a temperature of 75-80°C and a rotation speed of 500-700 r / min for 8-10 h, cool to room temperature and filter, and dry at 50°C for 24 h to obtain green high-multiplier foamed microspheres.
[0010] Furthermore, the weight proportions of the components in the aqueous phase are 1.8-2 parts of polyvinyl alcohol, 150-180 parts of sodium chloride, and 500-600 parts of deionized water.
[0011] Furthermore, the weight proportions of the components in the oil phase are 60 parts of methyl methacrylate, 24-30 parts of butyl acrylate, 0.24-0.32 parts of a crosslinking agent, 0.8-1.2 parts of a modified initiator, and 25-27 parts of a foaming agent.
[0012] Furthermore, the crosslinking agent is 1,3,5-triacryloylhexahydro-1,3,5-triazine. 1,3,5-triacryloylhexahydro-1,3,5-triazine contains a triazine ring structure and three propylene groups, which can not only enhance the mechanical properties and thermal stability of the polymer shell, but also effectively prevent or delay the penetration of gas through the dense network formed by the crosslinking reaction, significantly improving the gas barrier property of the polymer shell.
[0013] Further, the modified initiator is prepared by the following steps:
[0014] Step A1, adding 4,4'-dihydroxybenzophenone and triethylenediamine to tetrahydrofuran and stirring and mixing, then adding isocyanatepropyltriethoxysilane dropwise, stirring and reacting at 50°C for 18-20h, removing the solvent by vacuum distillation to generate a precipitate, filtering, washing the precipitate with deionized water, and vacuum drying at 60°C for 1h to obtain an intermediate; under the catalysis of triethylenediamine, the phenolic hydroxyl group in 4,4'-dihydroxybenzophenone reacts with the isocyanate group of isocyanatepropyltriethoxysilane, and the triethoxysilane structure is connected to the dibenzophenone structure through an urethane bond to obtain an intermediate;
[0015] Step A2, adding the intermediate to tetrahydrofuran to completely dissolve it, adding isopropanol and acetic acid, reacting for 5-7 days under nitrogen protection and ultraviolet light irradiation, pouring into deionized water to obtain a crude product, eluting with petroleum ether / ethyl acetate at a volume ratio of 1:1, and obtaining a modified initiator after column chromatography separation and purification. The intermediate is dissolved in the solvent tetrahydrofuran, and under ultraviolet light irradiation and acetic acid catalysis, the carbonyl group of the intermediate captures hydrogen atoms from isopropanol to form a hydroxyl group, and then a modified initiator containing a benzopinacol structure is obtained through dimerization.
[0016] Furthermore, the usage ratio of the 4,4'-dihydroxybenzophenone, triethylenediamine, tetrahydrofuran and isocyanatepropyltriethoxysilane is 10g:0.01g:70-80mL:34.66-36.97g.
[0017] Furthermore, the usage ratio of the intermediate, tetrahydrofuran, isopropanol and acetic acid is 20 g: 80-100 mL: 30-50 mL: 0.1-0.15 mL.
[0018] Furthermore, the wavelength of the ultraviolet light is 350nm and the irradiation intensity is 5-6mW / cm 3 .
[0019] Furthermore, the foaming agent is one of n-heptane and isooctane or a combination of the two in any ratio. N-heptane and isooctane with larger molecular weight have similar boiling points, are difficult to diffuse through the polymer shell, and have excellent expansion properties.
[0020] A green high-magnification foaming microsphere is prepared by the above preparation method.
[0021] Beneficial effects of the present invention:
[0022] The present invention uses methyl methacrylate and butyl acrylate as polymerization monomers and 1,3,5-triacryloylhexahydro-1,3,5-triazine as a crosslinking agent. Under the action of a modified initiator, suspension polymerization and crosslinking are performed to form a polymer shell, thereby wrapping the foaming agent inside the shell to obtain foamed microspheres. Firstly, the raw materials of the present invention do not use methacrylonitrile or vinylidene chloride, so that the production is safer, green and environmentally friendly, and the production cost is reduced. Selecting 1,3,5-triacryloylhexahydro-1,3,5-triazine as a crosslinking agent can form a dense crosslinking network, thereby improving the mechanical properties, thermal stability and gas barrier properties of the polymer shell.
[0023] The modified initiator prepared by the invention contains a benzopinacol structure. When the temperature is higher than 70 DEG C, the benzopinacol structure is heated to dissociate to form two diphenylhydroxymethyl free radicals, which are then formed into acrylic acid monomer free radicals through hydrogen transfer, and the acrylic acid monomer polymerization reaction is efficiently initiated. The initial polymerization product can be used as a macromolecular initiator to continue to initiate the polymerization reaction, and finally a methyl methacrylate / butyl acrylate cross-linked copolymer is formed and an interpenetrating network containing a siloxane chain segment and a diphenylmethanol structure is grafted. On the one hand, the diphenylmethanol structure can improve the high temperature resistance and toughness of the polymer shell, thereby further improving the foaming stability, heat resistance and toughness of the foaming microspheres in synergistic effect with the cross-linking agent. On the other hand, the siloxane chain segment can provide additional rotational freedom and flexibility, which helps the polymer shell to better fill the gap while maintaining the structural integrity, and enhance the gas barrier performance of the polymer shell. When the foaming microspheres are heated and expanded, the foaming agent inside the polymer shell is not easy to penetrate or overflow, thereby showing a higher foaming ratio. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] This embodiment provides a modified initiator, which is prepared by the following steps:
[0027] Step A1, add 10 g of 4,4'-dihydroxybenzophenone and 0.01 g of triethylenediamine to 70 mL of tetrahydrofuran, stir and mix, then dropwise add 34.66 g of isocyanatepropyltriethoxysilane, stir and react at 50°C for 18 h, remove the solvent by vacuum distillation to produce a precipitate, filter, wash the precipitate with deionized water, and vacuum dry at 60°C for 1 h to obtain an intermediate;
[0028] Step A2: 20 g of the intermediate was added to 30 mL of tetrahydrofuran to completely dissolve it, 80 mL of isopropanol and 0.1 mL of acetic acid were added, and the mixture was stirred under nitrogen protection and ultraviolet light with a wavelength of 350 nm at 5 mW / cm 3 The reaction was carried out under irradiation with an intensity of 1000 nm for 7 days, poured into deionized water and stirred to obtain a crude product, which was eluted with petroleum ether / ethyl acetate in a volume ratio of 1:1, and separated and purified by column chromatography to obtain a modified initiator.
[0029] Example 2
[0030] This embodiment provides a modified initiator, which is prepared by the following steps:
[0031] Step A1, add 10 g of 4,4'-dihydroxybenzophenone and 0.01 g of triethylenediamine to 75 mL of tetrahydrofuran, stir and mix, then dropwise add 35.74 g of isocyanatepropyltriethoxysilane, stir and react at 50°C for 19 hours, remove the solvent by vacuum distillation to produce a precipitate, filter, wash the precipitate with deionized water, and vacuum dry at 60°C for 1 hour to obtain an intermediate;
[0032] Step A2: 20 g of the intermediate was added to 40 mL of tetrahydrofuran to completely dissolve it, and 90 mL of isopropanol and 0.15 mL of acetic acid were added. The mixture was stirred under nitrogen protection and ultraviolet light with a wavelength of 350 nm at 6 mW / cm 3 The reaction was carried out under irradiation with an intensity of 1000 nm for 6 days, poured into deionized water and stirred to obtain a crude product, which was eluted with petroleum ether / ethyl acetate in a volume ratio of 1:1, and separated and purified by column chromatography to obtain a modified initiator.
[0033] Example 3
[0034] This embodiment provides a modified initiator, which is prepared by the following steps:
[0035] Step A1, add 10 g of 4,4'-dihydroxybenzophenone and 0.01 g of triethylenediamine to 80 mL of tetrahydrofuran, stir and mix, then dropwise add 36.97 g of isocyanatepropyltriethoxysilane, stir and react at 50°C for 20 h, remove the solvent by vacuum distillation to produce a precipitate, filter, wash the precipitate with deionized water, and vacuum dry at 60°C for 1 h to obtain an intermediate;
[0036] Step A2: 20 g of the intermediate was added to 50 mL of tetrahydrofuran to completely dissolve it, 100 mL of isopropanol and 0.15 mL of acetic acid were added, and the mixture was stirred under nitrogen protection and ultraviolet light with a wavelength of 350 nm at 6 mW / cm 3 The reaction was carried out under irradiation with an intensity of 1000 nm for 5 days, and the mixture was poured into deionized water and stirred to obtain a crude product, which was eluted with petroleum ether / ethyl acetate in a volume ratio of 1:1. After separation and purification by column chromatography, a modified initiator was obtained.
[0037] Comparative Example 1
[0038] The difference between this comparative example and Example 3 is that in step A1, isocyanatepropyltriethoxysilane is not used to react with 4,4'-dihydroxybenzophenone, and the other raw materials and steps are the same.
[0039] Example 4
[0040] A method for preparing green high-magnification foamed microspheres comprises the following steps:
[0041] (1) 1.8 g of polyvinyl alcohol and 150 g of sodium chloride were added to 500 g of deionized water and dissolved, and then stirred at 1000 r / min for 5 min to obtain an aqueous phase; 60 g of methyl methacrylate, 24 g of butyl acrylate, 0.24 g of 1,3,5-triacryloylhexahydro-1,3,5-triazine and 0.8 g of the modified initiator prepared in Example 1 were added to 25 g of n-heptane and mixed uniformly to obtain an oil phase;
[0042] (2) slowly adding the oil phase to the water phase at 10°C and stirring at 2000 r / min for 5 min to obtain an oil-in-water suspension dispersion;
[0043] (3) Pour the suspended dispersion into a reaction kettle, introduce nitrogen and evacuate for three cycles, then introduce nitrogen to increase the pressure in the kettle to 0.8 MPa, react at a temperature of 75°C and a rotation speed of 500 r / min for 8 h, cool to room temperature and filter, and dry at 50°C for 24 h to obtain green high-multiplicity foamed microspheres.
[0044] Example 5
[0045] A method for preparing green high-magnification foamed microspheres comprises the following steps:
[0046] (1) 1.9 g of polyvinyl alcohol and 170 g of sodium chloride were added to 560 g of deionized water for dissolution, and then stirred at 1000 r / min for 5 min to obtain an aqueous phase; 60 g of methyl methacrylate, 27 g of butyl acrylate, 0.28 g of 1,3,5-triacryloylhexahydro-1,3,5-triazine and 1 g of the modified initiator prepared in Example 2 were added to 26 g of a blowing agent, isooctane, and mixed uniformly to obtain an oil phase;
[0047] (2) At a temperature of 9° C., the oil phase was slowly added dropwise to the water phase and stirred at a speed of 2500 r / min for 5 min to obtain an oil-in-water suspension dispersion;
[0048] (3) The suspension dispersion was poured into a reaction kettle, and nitrogen was introduced and vacuumed for three cycles. Then, nitrogen was introduced to increase the pressure in the kettle to 0.7 MPa. The reaction was carried out at a temperature of 78°C and a rotation speed of 600 r / min for 9 h. After cooling to room temperature, the mixture was filtered and dried at 50°C for 24 h to obtain green high-multiplicity foamed microspheres.
[0049] Example 6
[0050] A method for preparing green high-magnification foamed microspheres comprises the following steps:
[0051] (1) 2 g of polyvinyl alcohol and 180 g of sodium chloride were added to 600 g of deionized water and dissolved, and then stirred at 1000 r / min for 5 min to obtain an aqueous phase; 60 g of methyl methacrylate, 30 g of butyl acrylate, 0.32 g of 1,3,5-triacryloylhexahydro-1,3,5-triazine and 1.2 g of the modified initiator prepared in Example 3 were added to 13 g of n-heptane and 14 g of isooctane and mixed uniformly to obtain an oil phase;
[0052] (2) At a temperature of 8°C, the oil phase was slowly added dropwise to the water phase and stirred at a speed of 3000 r / min for 5 min to obtain an oil-in-water suspension dispersion;
[0053] (3) Pour the suspended dispersion into a reaction kettle, introduce nitrogen and evacuate for three cycles, then introduce nitrogen to increase the pressure in the kettle to 0.5 MPa, react at a temperature of 80°C and a rotation speed of 700 r / min for 10 h, cool to room temperature and filter, and dry at 50°C for 24 h to obtain green high-multiplicity foamed microspheres.
[0054] Comparative Example 2
[0055] The difference between this comparative example and Example 6 is that the modified initiator prepared in Comparative Example 1 is used to replace the modified initiator prepared in Example 3 in equal amount, and the other raw materials and steps are the same.
[0056] Comparative Example 3
[0057] The difference between this comparative example and Example 6 is that azobisisovaleronitrile is used as an initiator to replace the modified initiator prepared in Example 3 in equal amounts, and the other raw materials and steps are the same.
[0058] Comparative Example 4
[0059] This comparative example is different from Example 6 in that trimethylolpropane trimethacrylate is used as a cross-linking agent to replace 1,3,5-triacryloylhexahydro-1,3,5-triazine in equal amounts, and the remaining raw materials and steps are the same.
[0060] The performance of the foamed microspheres prepared in Examples 4 to 6 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:
[0061] Table 1
[0062] project Example 4 Example 5 Example 6 Comparative Example 2 Comparative Example 3 Comparative Example 4 Average particle size / μm 25.6 26.4 27.1 26.2 24.7 28.5 <![CDATA[T s / ℃]]> 124.9 124.1 123.6 122.7 102.3 113.4 <![CDATA[T max / ℃]]> 202.5 205.2 208.7 178.6 142.8 169.3 Diameter expansion ratio 76.8 77.9 79.3 69.4 64.2 68.1
[0063] It can be seen from the data in Table 1 that the foamed microspheres prepared in Examples 4 to 6 have a stable initial foaming temperature T s , and has a higher maximum foaming temperature T max, with a wider stable foaming temperature range, indicating that the foamed microspheres have good heat resistance; the diameter expansion ratios obtained are all above 76 times, indicating that the prepared foamed microspheres have good expansion ratios, and the shell material has excellent toughness and gas barrier properties.
[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing green high-magnification foamed microspheres, characterized in that: The following steps are involved: (1) adding polyvinyl alcohol and sodium chloride to deionized water to dissolve, and then stirring at 1000 r / min for 5 minutes to obtain an aqueous phase; adding methyl methacrylate, butyl acrylate, a crosslinking agent and a modified initiator to a foaming agent and mixing them uniformly to obtain an oil phase; (2) slowly adding the oil phase to the water phase at a temperature of 8-10° C. and stirring at a speed of 2000-3000 r / min for 5 min to obtain an oil-in-water suspension dispersion; (3) Pour the suspension dispersion into a reaction kettle, introduce nitrogen, and then evacuate and circulate, then introduce nitrogen to increase the pressure to 0.5-0.8 MPa, react at a temperature of 75-80°C and a rotation speed of 500-700 r / min for 8-10 hours, cool to room temperature, filter, and dry to obtain green high-multiplier foaming microspheres.
2. The method for preparing green high-magnification foamed microspheres according to claim 1, characterized in that: The weight proportions of the components in the water phase are 1.8-2 parts of polyvinyl alcohol, 150-180 parts of sodium chloride, and 500-600 parts of deionized water.
3. The method for preparing green high-magnification foamed microspheres according to claim 1, characterized in that: The weight proportions of the components in the oil phase are 60 parts of methyl methacrylate, 24-30 parts of butyl acrylate, 0.24-0.32 parts of a crosslinking agent, 0.8-1.2 parts of a modified initiator, and 25-27 parts of a foaming agent.
4. The method for preparing green high-magnification foamed microspheres according to claim 1, characterized in that: The cross-linking agent is 1,3,5-triacryloylhexahydro-1,3,5-triazine.
5. The method for preparing green high-magnification foamed microspheres according to claim 1, characterized in that: The modified initiator is prepared by the following steps: Step A1, adding 4,4'-dihydroxybenzophenone and triethylenediamine to tetrahydrofuran and stirring to mix, then adding isocyanatepropyltriethoxysilane dropwise, stirring to react at 50°C for 18-20h, distilling under reduced pressure to produce a precipitate, filtering, washing the precipitate with deionized water, and vacuum drying at 60°C for 1h to obtain an intermediate; Step A2, adding the intermediate into tetrahydrofuran to completely dissolve it, adding isopropanol and acetic acid, reacting for 5-7 days under nitrogen protection and ultraviolet light irradiation, pouring into deionized water to obtain a crude product, eluting, separating and purifying by column chromatography to obtain a modified initiator.
6. The method for preparing green high-magnification foamed microspheres according to claim 5, characterized in that: The usage ratio of the 4,4'-dihydroxybenzophenone, triethylenediamine, tetrahydrofuran and isocyanatepropyltriethoxysilane is 10g:0.01g:70-80mL:34.66-36.97g.
7. The method for preparing green high-magnification foamed microspheres according to claim 5, characterized in that: The usage ratio of the intermediate, tetrahydrofuran, isopropanol and acetic acid is 20 g: 80-100 mL: 30-50 mL: 0.1-0.15 mL.
8. The method for preparing green high-magnification foamed microspheres according to claim 5, characterized in that: The wavelength of the ultraviolet light is 350nm, and the irradiation intensity is 5-6mW / cm 3 .
9. The method for preparing green high-magnification foamed microspheres according to claim 1, characterized in that: The foaming agent is one of n-heptane and isooctane or a combination of the two in any ratio.
10. A green high-magnification foamed microsphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.